EXPLORING SUSTAINABLE TEA TOURISM IN NILGIRIS: A MULTI-DIMENSIONAL APPROACH TO GROWTH AND CONSERVATION - PALANIYANDI, ASHOKKUMAR; C P, DR SANGEETHA (Turizam, 2025)
In an era where sustainable development is paramount, tea tourism has emerged as a dynamic convergence of cultural heritage, economic opportunity, environmental stewardship, and technological innovation. This study examines sustainable tea tourism practices in the Nilgiris District of Tamil Nadu, India, by integrating quantitative and qualitative research methodologies. A structured questionnaire was administered to 126 tea growers, tea manufacturers and other key stakeholders, while in-depth interviews and focus group sessions enriched the data, particularly in understanding the operational challenges associated with eco-friendly initiatives. Structural Equation Modeling (SEM) revealed that community collaboration, economic empowerment, and technological/infrastructural support each exert a significantly positive impact on sustainable tea tourism practices. Conversely, eco-friendly practices were found to have a negative coefficient, a finding that was further clarified through qualitative insights—highlighting issues such as high initial capital outlay, insufficient training, and policy limitations. The study underscores the importance of a holistic approach in which technological investments and enhanced community participation mitigate the challenges tied to sustainable environmental practices. These findings provide actionable recommendations for policymakers, tea estate managers, and tourism professionals aimed at reinforcing sustainable practices within the tea tourism ecosystem. Additionally, the study discusses its limitations and suggests potential directions for future research.
Keywords: Community Collaboration; Economic Empowerment; Eco-friendly Practices; Sustainable Tea Tourism; Technological Integration